Transformation of Values in Social Preferences: The Impact of Legal Rules on Changes in Social Norms in Society - Inni Hajatika; Evi Dwi Hastri; Abintoro Prakoso (Res Judicata Law Review, 2024)
This study aims to analyze how the rule of law affects the transformation of social values and preferences, as well as its impact on changes in social norms in society. With a juridical-normative approach and socio-legal analysis, this study explores the relationship between written law and social dynamics that lead to the formation of new norms. This study uses a non-doctrinal research method, namely socio-legal. In this research, the approach used is an interdisciplinary approach, especially in the study of legal anthropology, which in essence is the legal behavior of the community, the legal culture of the community, and the public's perspective on the law and its derivative products. Then a conclusin drawing or verification is carried out. The results of the study show that the rule of law not only reflects the values that exist in society but also plays an active role in shaping and changing social preferences. Legal rules that are applied effectively can influence individual and collective behavior, resulting in new social norms that are more in line with the goals of the law. However, this adaptation of social norms is also influenced by other factors such as culture, education, and economic conditions. This study concludes that the transformation of values in social preferences is a dynamic process that involves a complex interaction between legal rules and social conditions of society. Legal rules that are responsive to social change can serve as an effective tool to encourage positive change in social norms, while mismatches between laws and social preferences can lead to resistance and non-compliance.